(untitled) (Al-Aasar, 2025)
This scholarly inquiry investigates the conveyance of Reminiscence and spatial uprooting in the segregation literature of southern Asia through a critical analysis of Pinjar by Amrita Pritam and Toba Tek Singh by SaadatHasanManto. Its objective is to explore how literary narratives map trauma into geographical and emotional landscapes transforming space into a symbol of historical breakup and cultural loss. Anchored in the theory of trauma particularly the work of Cathy Caruth and that are based on concepts of memory nostalgia and displacement.The analysis uses qualitative textual methods to examine how Pinjar builds the female body as a confined and traumatized site within the fractured geography of the partition while Toba Tek Singh satirizes the absurdity of the statelessness and the psychological disintegration induced by forced migration. The study is guided by two central questions: (1) How do partition narratives organize spatially to reflect inter-generational memory and suffering? (2) How do literary spaces work as counterattacks that recover suppressed stories?. By placing trauma within the symbolic geography of literature this research contributes to partition studies and literary trauma theory by offering a nuanced reading of how personal and collective memory is part of and through space. It shows that literary texts not only narrate the loss but also build alternative memory cartographies that official stories resist and get involved with the emotional consequences of displacement.